Trauma, relational trust and the effects on the midwife : a thesis presented in fulfillment of the requirements for the degree of Doctor of Philosophy, School of Health and Social Sciences, Massey University, Palmerston North, New Zealand - Calvert, Irene (Massey University, 2011)
This qualitative thesis uses a method of narrative research to explore the effects of a traumatic practice experience on the 16 midwives interviewed for this project. It is an investigation of relationships at play influenced by power games and their consequences creating conflict. The issues of partnership and autonomous midwifery practice are the key drivers that make New Zealand midwives more likely to be blamed and their competence in practice challenged. Partnership negates domination for collaboration and as a result challenges the beliefs of the dominant groups of medicine and management. Midwives questioned why when they had coped with similar situations in the past was this incident ‘the straw that broke the camels back’. The investigation uncovers that the trauma experienced was prolonged due to a breakdown of relational trust in organisations, management, colleagues, women and self. The breach of trust altered the meaning of the traumatic event for the midwives which impacted on their personal and professional identities creating biographical disruption and exacerbating the initial stress reaction. Loss of personal and professional identities elicited grief which in most cases was disenfranchised and therefore not supported. Grief associated with maternal death was supported. As a result of the increase of emotional stress some of the midwives suffered illness such as anxiety, post traumatic stress disorder and chronic back pain implying that the aetiology of the disease could be emotions. These illnesses experienced by the midwives contributed to workforce attrition. Midwifery has an oral history whereby relationships are built and experiences shared, making narrative research an ideal method for this personal topic. The analysis of the study data draws upon the narrative concepts of Margaret Somers (1994), Arthur Frank (2005) and Davis and Harre (1990) and Bourdieu (1982) theory of economic practice to facilitate an understanding of the effects of these traumatic practice experiences for the midwife participants. Midwives in New Zealand are legally required to provide care to childbearing women using a partnership model of care based on trust and mutual respect (MCNZ,2004). Consideration was given to the influence of the model on the effects experienced by the midwives. Substantive chapters explore the effects of biographical disruption, grief, support, violence in the workplace, destroyed relationships and disrupted lives, trust and dysfunctional organisations. In the text gathered from this study I have developed two theoretical models; one explains how the trauma is exacerbated rather than supported; the other outlines the effects of the trauma. The study adds to the literature by providing evidence that biographical disruption occurring as a result of a traumatic practice experience can lead to a chronic illness. My research has addressed gaps in midwifery, biographical disruption, grief, workplace violence and trauma literature.
Keywords: Midwifery; Midwives; Job stress; Workplace conflict; Interpersonal relations; Midwife health; Professional relationships; Workplace trauma